THE IMPACT OF PROJECT BASED LEARNING TOWARDS CREATIVE THINKING AND SCIENTIFIC ATTITUDES - Didi Nur Jamaludin; Suroso Adi Yudianto; Topik Hidayat; Nukhbatul Bidayati Haka (Science Education, Institut Agama Islam Negeri Ponorogo, 2026)
Project-based learning (PjBL) is a learning model that develops thinking and science process skills in problem-solving. Method using a quasi-experimental research design with a matching-only pretest-posttest control group design. The study population consisted of all 10th-grade students at Bandung State Senior High School, and the study used cluster random sampling. The research instrument used a creative thinking essay test and a scientific attitude questionnaire. The research analysis used a t-test and N-Gain. The results of the study indicate that project-based learning can significantly improve creative thinking compared to conventional learning (0.001 < 0.05). The process of determining fundamental questions and monitoring in project learning plays an important role in developing creative thinking ability. Another important thing in PjBL is providing feedback according to learning objectives when assessing results and evaluating experiences. Scientific attitudes showed a low increase, thus showed insignificantly difference analysis (0.069 < 0.05). This is due to external factors such as personality, information, group affiliation, and the limitations of the assessment scale in the questionnaire. The further PjBL research challenges related to the use of scientific attitude instruments with a larger assessment scale, technology integration, multidisciplinary approach, developing science process skills, higher-order thinking skills (HOTS), and 21st-century competencies.